Mathematical Word Problems That Contain a Constant in the Course of Mathematics of Primary School in Ukraine - Skvortsova, Svitlana; Оnoprienko Oksana; Romanyshyn, Ruslana (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The article is devoted to the research of the place of the mathematical word problems in the course of mathematics of primary school in Ukraine. The researchers define the results in the study of solving math problems, find out the essence of the process of solving math problems, form primary school students’ ability to solve math problems that contain a constant. Among the mentioned are to find the fourth proportional, do the proportional division and find the unknown number by two differences. The paper deals with the organization of educational research of students in order to identify common and distinctive features of the mathematical structures of these types of math problems and their influence on the method of solution. Based on the methodological system of teaching primary school learners to solve math problems by S. Skvortsova, taking into account the essence of the concept of “ability to solve math problems” and the methodical system of forming the ability to solve certain types of math problems, it has been proposed a system of drilling activities for the generalization of mathematical structures and methods of solving math problems that contain a constant value.